The Effect of Location, Service Quality and Price on Consumer Purchasing Decisions (Case Study on Consumers of Mak Hengky Restaurant Air Manna South Bengkulu) - Herry Novrianda; Lestari Lestari; Marliza Ade Fitri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Purchasing decision is a process where consumers evaluate various alternative choices and choose one or more alternatives that are needed based on certain considerations. Several factors influence consumer purchasing decisions including location, service quality and price. This study aims to determine the effect of location, service quality and price on consumer purchasing decisions. This type of research is quantitative research with a descriptive approach. The population of this study were all consumers of the Mak Hengky Air Manna restaurant. The number of research samples was 85 people. Data collection was carried out using a questionnaire. The data analysis technique uses multiple linear regression analysis techniques. The results of data analysis obtained multiple linear regression equations as follows: Y = 1.752 + 0.373 X1 + 0.301 X2+ 0.302 X3. The results of the analysis show that partially location has a positive and significant effect on purchasing decisions (tcount = 4,799 and Sig = 0,000), service quality has a positive and significant effect on purchasing decisions (tcount = 4,615 and Sig = 0,000) and price has a positive and significant effect on purchasing decisions (tcount = 3.836 and Sig = 0.000). Simultaneously there is the influence of location, service quality and price on consumer purchasing decisions (Fcount = 114,832 and Sig = 0,000). It is suggested to the owner of the Mak Hengky restaurant to be able to improve consumer purchasing decisions by providing good parking space, improving service quality and setting competitive prices according to consumer perceptions.